2012
DOI: 10.3109/01942638.2012.739269
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Norwegian Version of the Children's Assessment of Participation and Enjoyment (CAPE) and Preferences for Activities of Children (PAC)

Abstract: Abstract.This study examined test-retest reliability of the Norwegian version of Children's Assessment

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…As did previous studies (Imms, 2008;King et al, 2004, the Norwegian study (Nordtorp, Nyquist, Jahnsen, Moser & Strand, 2013) emphasises that the enjoyment dimension should be used with caution, especially as an outcome measurement. On the basis of the studies conducted by Bult et al (2010), King et al (2004) and Nordtorp et al (2013), it can be concluded that the reliability of the diversity and frequency dimensions is satisfactory.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As did previous studies (Imms, 2008;King et al, 2004, the Norwegian study (Nordtorp, Nyquist, Jahnsen, Moser & Strand, 2013) emphasises that the enjoyment dimension should be used with caution, especially as an outcome measurement. On the basis of the studies conducted by Bult et al (2010), King et al (2004) and Nordtorp et al (2013), it can be concluded that the reliability of the diversity and frequency dimensions is satisfactory.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of the studies conducted by Bult et al (2010), King et al (2004) and Nordtorp et al (2013), it can be concluded that the reliability of the diversity and frequency dimensions is satisfactory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural adaptation studies often present psychometric properties of the translated version of the questionnaire but not results of the translation or how the items were culturally adapted (Ullenhag et al, 2012a; Nordtorp et al, 2013, Bult et al, 2010; Stofel & Berg, 2008). An exception is a study by Costa (2014) that translated and culturally adapted the Austrian-German Perceived Efficacy and Goal Setting System (PEGS) by interviewing 23 occupational therapists and a 14 year-old boy.…”
Section: Discussionmentioning
confidence: 99%
“…Several children’s participation and activity measures have been culturally adapted to ensure the relevance of the measure to a specific culture (Costa, 2014; Bult et al, 2010; Ullenghag et al, 2012a; Ullenghag et al, 2012b; Stofel & Berg, 2008; Nordtorp et al, 2013). Cultural adaptation improves consistency in the face and content validity between the original and culturally adapted versions of a measure (Guillemin et al, 1993).…”
Section: Introductionmentioning
confidence: 99%